Visceral adipose tissue and cardiometabolic risk factors in young Hispanic and non-Hispanic girls - Bland, Victoria L.; Kindler, Joseph M.; Blew, Robert M.; Morrill, Kristin E.; Roe, Denise J.; Going, Scott B. (Frontiers in Pediatrics, 2022)
Background Risk factors for cardiometabolic diseases (e.g., type 2 diabetes, cardiovascular disease) can begin developing in childhood. Elevated body mass index (BMI) is associated with greater likelihood of developing such diseases; however, this relationship varies by race and ethnicity. Notably, Hispanics tend to have high rates of obesity and are disproportionately affected by type 2 diabetes. We aimed to determine if visceral adiposes tissue (VAT) is associated with cardiometabolic risk factors (i.e., triglycerides, cholesterol, insulin resistance, C-reactive protein, and blood pressure), independent of BMI percentile, in a sample of primarily Hispanic adolescent girls. Methods and results A total of 337 girls (73% Hispanic) took part in the cross-sectional study. Hispanic girls generally had greater BMI percentile, VAT, and cardiometabolic risk factors compared to non-Hispanic girls. Multiple linear regression was used to assess the relationships between Dual-energy X-ray Absorptiometry (DXA)-derived VAT and cardiometabolic outcomes, controlling for BMI percentile (<85th percentile or ≥85th percentile), age, ethnicity (Hispanic/non-Hispanic), and Tanner stage. Significant interactions between VAT and BMI percentile were identified for almost all cardiometabolic outcomes. Upon stratification, the association between VAT and cardiometabolic outcomes was strongest in girls ≥85th BMI percentile, as compared to girls <85th percentile. However, VAT was only significantly associated with higher triglycerides (girls ≥85th percentile) and higher insulin resistance (both BMI percentiles) after stratification. Conclusion VAT was associated with increased triglycerides and insulin resistance in girls with overweight or obesity. These findings warrant further investigation between VAT and cardiometabolic health in Hispanic adolescents who tend to accumulate more adipose tissue during adolescence.